The Effect of Vitamin E, &Bgr;-Carotene, and Acidophilus Probiotics on The Salivary Gland Flow Rate in Streptozotocin-Induced Diabetes in Rats: An in-vivo Study - Felemban MF; Bin Mubayrik AF; Alotaibi O (Clinical, Cosmetic and Investigational Dentistry)
Mutaz Fahad Felemban,* Azizah F Bin Mubayrik,* Ohoud Alotaibi* Oral Medicine and Diagnostic Science Department, College of Dentistry, King Saud University, Riyadh, Saudi Arabia*These authors contributed equally to this workCorrespondence: Mutaz Fahad Felemban, Oral Medicine and Diagnostic Science Department, College of Dentistry, King Saud University, Riyadh, Saudi Arabia, Email Moatazfelemban@gmail.comPurpose: Diabetes is closely linked to reduced salivary flow rate, contributing to oral complications such as infections, dental caries, and periodontal disease. Vitamin E, β-carotene, and probiotics may help counteract these effects by neutralizing reactive oxygen species, reducing cellular damage, and preserving glandular function. This study aimed to evaluate the effects of the effect of vitamin E, β-carotene, and probiotics blend on the salivary glands of rats with Streptozotocin (STZ)-induced diabetes, addressing gaps in current research.Methods: Eighty rats were induced with diabetes using a single intraperitoneal injection of STZ (60 mg/kg). They were randomly divided into control and experimental groups, which were further subdivided into ten subgroups: 2-week and 4-week saline, oil, vitamin E, β-carotene, and Probiotic Blend. Supplementation was administered daily via oral gavage. Salivary flow rate (SFR) was measured at three time points: before diabetes induction, after induction, and following supplementation, using pre-weighed cotton balls. Data were analyzed using SPSS.Results: There was a significant reduction in SFR after diabetes induction (pre-diabetes: M=1.1 mL, SD=0.42; post-diabetes: M=0.6 mL, SD=0.24; t=12.925, p=0.000). On the day of sacrifice, Mann–Whitney U-tests showed significant differences in SFR between groups (p=0.000). The Kruskal–Wallis test also indicated significant differences across all groups (p< 0.001). After 2 weeks, the highest SFR was observed in the vitamin E group (1.0 mL), followed by β-carotene (0.9 mL) and probiotics (0.8 mL), while the saline group recorded the lowest (0.3 mL). After 4 weeks, vitamin E again showed the highest SFR (1.1 mL), followed by β-carotene (0.9 mL), probiotics (0.7 mL), and oil (0.7 mL), with saline remaining the lowest (0.4 mL).Conclusion: This study highlights the potential of vitamin E, β-carotene, and probiotics as alternative therapies for managing diabetes-related hyposalivation. Further research is required to validate their role in improving oral health among diabetics.Keywords: diabetes, salivary flow rate, vitamin E, β-carotene, acidophilus probiotic